Krzątanina Brach-Czainy – myślenie ciałem. Między metaforą a wiedzą - Przymuszała, Beata (Humaniora. Czasopismo Internetowe, 2021)
The article presents problems with the interpretation of the category of everyday life in the essays by Jolanta Brach-Czaina.The „krzątactwo” metaphor changes thinking about the reality around us. The „krzątctwo” as a form of being in the world combines corporeality with reflection, challenging strong boundaries between disciplines.